Extracellular Matrix in Synthetic Hydrogel‐Based Prostate Cancer Organoids Regulate Therapeutic Response to EZH2 and DRD2 Inhibitors (Adv. Mater. 2/2022). Issue 2 (13th January 2022) - Mosquera, Matthew J.; Kim, Sungwoong; Bareja, Rohan; Fang, Zhou; Cai, Shuangyi; Pan, Heng; Asad, Muhammad; Martin, Maria Laura; Sigouros, Michael; Rowdo, Florencia M.; Ackermann, Sarah; Capuano, Jared; et al.
Abstract : Cancer Therapy In article number 2100096, Olivier Elemento, Ankur Singh, and co‐workers examine the prostate cancer tumor microenvironment using multi‐omics techniques and report a prostate cancer organoid bioengineered using a modular synthetic hydrogel that shapes the epigenetics and transcriptomics of cancer cells. They discover the "dopamine receptor" pathway as a targeted therapy for epigenetically reprogrammed neuroendocrine prostate cancers.